Primary pulmonary undifferentiated pleomorphic sarcoma (PPUPS) - Qorbani, Amir; Nelson, Scott D (Autopsy and Case Reports, 2019)
Undifferentiated pleomorphic sarcoma (UPS) is a high-grade pleomorphic neoplasm with no identifiable line(s) of differentiation using currently available diagnostic techniques. Therefore, it is essentially a diagnosis of exclusion, which requires generous tissue sampling, adequate contextually interpreted immunohistochemistry, and relevant molecular studies. UPS is a common soft tissue sarcoma (historically one of the entities referred to as malignant fibrous histiocytoma (MFH)), which can develop in various organs, but lung involvement is usually due to metastasis. Primary Pulmonary UPS (PPUPS) is exceptionally rare and here we present a 66-year-old man who presented with anemia and weight loss, found to have a 17 cm right lung mass with invasion to the chest wall and diaphragm. Extensive sampling and immunohistochemistry studies failed to reveal any line of differentiation. Upon exclusion of a possible extrapulmonary origin, a diagnosis of PPUPS was rendered. In addition, we reviewed all 84 previously reported cases of PPUPS/PPMFH in the literature since 1979 and summarized the clinical information.